Drying Methods Affecting the Antioxidant Activity of Turmeric Crude Drug - Anila Wirantika; Idda Nuriya Rahma; Raafi Akbar Putra; Devita Almayda; Diah Ayu Kusumawati; Muhammad Agil Nur Fauzan; Yeti Rusmiati Hasanah; Afwa Hayuningtyas; Pinyapat Jitphongsaikul; Alwani Hamad (Universitas Muhammadiyah Purwokerto, 2023)
Turmeric is commonly a spice with many benefits in improving health, including antioxidants, anti-inflammatory and antimicrobial properties. The preparation of turmeric crude drug usually uses conventional sun drying. However, the quality of crude drugs is uncontrollable. The alternative using a modern drying process may affect the antioxidant properties of the final crude drug. This research aims to investigate the effect of drying methods (cabinet drying at 30oC and 70oC, infrared (IR), and conventional sun drying) on the antioxidant activity of turmeric crude drugs. The moisture content and its chemical compounds, including Total Phenolic Content (TPC) and Total Flavonoid Content (TFC), were also investigated. Antioxidant activity was measured using DPPH free radical scavenging and Feri Reducing Antioxidant Power (FRAP) method. The results showed that the moisture content of dried turmeric samples from cabinet drying at 70 C and sun drying was less than 10%. TPC of all dried turmeric from modern drying methods was significantly higher than conventional sun drying and the same as TFC results, except for the sample from the IR method. The antioxidant activity of dried curcumin from IR drying was significantly higher than that of another sample in the FRAP method. However, the higher antioxidant of dried turmeric using the DPPH free radical scavenging showed in dried turmeric from cabinet drying at 70 C and sun drying. The results of the antioxidant activity of the dried turmeric crude drug did not correlate with the TPC and TFC data as predicted using Pearson’s Correlation. Thus, it can be concluded that the drying methods influenced the antioxidant activity of turmeric crude drug, and it did not correlate with phenolic and flavonoid content.